Peran Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) dalam Pemerataan Pendidikan Tinggi bagi Masyarakat di Kalimantan Tengah - Karbila, Ibnu Hasan (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2024)
Higher education is the main pillar in producing superior, competitive human resources (HR), and able to drive sustainable national development. Conditions that are not yet in harmony occur in Central Kalimantan where the Gross Participation Rate for higher education in 2024 is still relatively low, which is 27.49%. This low Gross Participation Rate reflects the inequality of access to education between urban and rural areas. Factors that cause this low figure include Geographical and Accessibility conditions, Socio-Economic Conditions, Lack of Higher Education Institutions, Culture and Awareness of Education and Lack of Information and Assistance. The problem statement in this Policy Paper is the Socio-Economic Conditions of the community in Central Kalimantan. The writing of this Policy Paper uses a descriptive qualitative method, the data collection techniques used are observation, interviews, and documentation. The results show that the majority of the population of Central Kalimantan works in the informal and agricultural sectors, making income still low and vulnerable to social and economic inequality which has an impact on the low Gross Participation Rate. The policy options offered in this Policy Paper to overcome this problem are by creating technical guidelines for expanding affirmative programs by the Directorate General of Islamic Education, which is expected to be the best solution and policy alternative in resolving the problem of low participation in higher education.